Transaction cost unbundling and investors’ reliance on investment research: Evidence from experimental asset markets - Stirnkorb, Sebastian (Accounting, Organizations and Society, 2024)
Broker-dealers traditionally charge their clients for the provision of investment research with a composite fee that bundles payments for research with other variable fees, such as those for trade executions. Due to regulatory changes in Europe, US broker-dealers temporarily allowed some of their clients to pay an explicit fee for the provision of investment research. Drawing on the sunk cost literature, I examine how transaction cost unbundling influences investors’ reliance on investment research. Results from 16 experimental markets indicate that investors place greater weight on costly forecasts under a system of unbundled payments compared to bundled payments, but only if transaction costs are sufficiently high, which is consistent with the dynamics of a sunk cost fallacy. I find marginal evidence that the enhanced focus on the forecast further inhibits investors' learning, as reflected in a slower reduction of price errors over time. These results are important since investors worldwide are increasingly paying explicit charges for investment research, a trend reinforced by a recent SEC policy change.